Kryterium przedmiotowe nieruchomości - Lechowicz, Tomasz (Gospodarka w Praktyce i Teorii, 2011)
The concept of property is governed by law and shows the similarity of many countries. On the basis of American law in the composition of the estate includes, objects permanently connected with land or natural objects that are connected to their roots, for instance, artificial trees and objects that were created by man, such as buildings, structures. The property also includes land, minerals that are beneath the surface, and the space above the ground The definition of property in force in Poland, included in the Civil Code provides that (...)properties are part of the earth surface, forming a separate object of property (land) as well as buildings permanently connected with land or parts of such buildings, where, under special provisions are separate from the land the subject property . Buildings and parts thereof, or premises shall be property only then, when this provides a special rule. When there is no such regulation is part of building land. Properties of the component parts - that everything that cannot be removed without damage or significant change of disconnected - include: · Buildings and other devices permanently associated with the land · Land · Water · The trees standing, and other plants from the moment of sowing or planting · Mineral deposits which are not properties of SP